Jarl Sigvaldi and the battle at Svoldr in the saga tradition - Morawiec, Jakub (Wydawnictwo Naukowe UAM, 2009)
The battle of Svoldr is one of the most significant events described by Icelandic sagas. According to them, Sigvaldi, the legendary jarl of Jomsborg also took part in the encounter as one of enemies of the Norwegian king Olaf Tryggvason, who fell in the battle. Saga authors rely in this case, among others, on particular skaldic stanzas that are said to refer to Sigvaldi and his treachery against king Olaf. The aim of the paper is to investigate ways this tradition was constructed and its historical reliability.
Keywords: Sagas; Skaldic poety; Prosi metrum; Sigvaldi